The Dynamics of Loan Sales and Lender Incentives - Gryglewicz, Sebastian; Mayer, Simon; Morellec, Erwan (Review of Financial Studies, 2024)
Abstract How much of a loan should a lender retain, and how do loan sales affect loan performance? We address these questions in a model in which a lender originates loans that it can sell to investors. The lender reduces default risk through screening at origination and monitoring after origination, but is subject to moral hazard. The optimal lender-investor contract can be implemented by requiring the lender to initially retain a share of the loan that it gradually sells to investors, rationalizing loan sales after origination. The model generates novel predictions linking loan and lender characteristics to initial retention, sales dynamics, and loan performance.